Association Between Mother’s Age and Breastfeeding Status in the Northern Iran - Veghari, G (Journal of Nepal Paediatric Society, 2015)
Introduction: Breast milk provides the ideal nutrition for infant and it is more easily digested than infant formula. The main aim of this study is to determine breastfeeding status, exclusive breastfeeding, and their relation with mother’s age among under-five children in the north of Iran. Material and Methods: This was a descriptive, cross-sectional study, which was carried out in 1997 persons (535 = Fars-native, 773 = Turkman and 689 = Sisstani) from 20 villages in the north of Iran. The calculated sample sizes of 1800 respondents at least were needed for a 95% confidence and a maximum marginal error 0.02. Exclusive Breastfeeding Duration (EBFD) and Breastfeeding Duration (BFD) were classified based on WHO definitions. Results: BFD is 20.16 months and statistical difference is significant among three ethnic groups (p=0.001). Post hoc test are significant between Fars-native and Turkman (p=0.001), and between Turkman and Sisstani (p=0.002) and between Fars-native and Sisstani (p=0.024). EBFD is 5.77 months and statistical difference is significant among three ethnic groups (p=0.011). Post hoc test is significant between Turkman and Sisstani (p=0.027). As whole, duration of breastfeeding positively increased with mother’s age (p=0.002) but statistical association was not significant between exclusive breastfeeding duration and mother’s age. Conclusion: In rural area in the north of Iran, the EBFD and BFD were 5.74 and 20.16 months, respectively and they were in Turkman group more than in others. Mother’s age have a rising role for EBFD and BFD whereas in all of ethnic groups it was not the same. J Nepal Paediatr Soc 2015;35(1):1-5